Smectite formation in the presence of sulfuric acid: Implications for acidic smectite formation on early Mars. (1st January 2018) - Peretyazhko, T.S.; Niles, P.B.; Sutter, B.; Morris, R.V.; Agresti, D.G.; Le, L.; Ming, D.W.
Abstract: The excess of orbital detection of smectite deposits compared to carbonate deposits on the martian surface presents an enigma because smectite and carbonate formations are both favored alteration products of basalt under neutral to alkaline conditions. We propose that Mars experienced acidic events caused by sulfuric acid (H2 SO4 ) that permitted phyllosilicate, but inhibited carbonate, formation. To experimentally verify this hypothesis, we report the first synthesis of smectite from Mars-analogue glass-rich basalt simulant (66 wt% glass, 32 wt% olivine, 2 wt% chromite) in the presence of H2 SO4 under hydrothermal conditions (∼200 °C). Smectites were analyzed by X-ray diffraction, Mössbauer spectroscopy, visible and near-infrared reflectance spectroscopy and electron microprobe to characterize mineralogy and chemical composition. Solution chemistry was determined by Inductively Coupled Plasma Mass Spectrometry. Basalt simulant suspensions in 11–42 mM H2 SO4 were acidic with pH ≤ 2 at the beginning of incubation and varied from acidic (pH 1.8) to mildly alkaline (pH 8.4) at the end of incubation. Alteration of glass phase during reaction of the basalt simulant with H2 SO4 led to formation of the dioctahedral smectite at final pH ∼3 and trioctahedral smectite saponite at final pH ∼4 and higher. Anhydrite and hematite formed in the final pH range from 1.8 to 8.4 while natroalunite was detected at pH 1.8. Hematite was precipitated as a result of oxidative dissolution of olivine present in Adirondack basalt simulant. Formation of secondary phases, including smectite, resulted in release of variable amounts of Si, Mg, Na and Ca while solubilization of Al and Fe was low. Comparison of mineralogical and solution chemistry data indicated that the type of smectite (i.e., dioctahedral vs trioctahedral) was likely controlled by Mg leaching from altering basalt and substantial Mg loss created favorable conditions for formation of dioctahedral smectite. We present a model for global-scale smectite formation on Mars via acid-sulfate conditions created by the volcanic outgassing of SO2 in the Noachian and early Hesperian.